KORBAN BULLYING DAN KONDISI PSIKOLOGIS SISWA SMP NEGERI 1 PEKANBARU - Fiska Dwi Rahmadani; Zulfan Saam; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study is based on the researcher’s experience during the internship at the school, showing that there are some students who experience bullying and phenomena that occur in the educational field. This study is aimed to determine the general description of bullying victims and the psychological conditions of bullied students at the school. The research method is a quantitative method along with the descriptive approach. The subject of this research is the eight grade students of Junior High School 1 Pekanbaru. The instrument of data collection is a questionnaire by using modified Likert Scale. Based on the data analysis, generally the level of students experiencing bullying at the school shows a moderate level in proportion. Based on the bully indicator, most students experienced; verbal bullying, mental bullying, and physical bullying. Based on gender, more bullying experienced by male students rather than female students. Psychological conditions of the students experiencing bullying stand at moderate level which is dominated by emotional aspects and then stress.Keywords: Bullying Victims, Psychological Conditions, Student